Statistical optimization of BG11 medium for enhanced zeaxanthin productivity in Synechococcus marinus (NIOT-208) - S.PRIYANKA; R. KIRUBAGARAN; J.T. MARY LEEMA (International Journal of Pharma and Bio Sciences, 2019)
Zeaxanthin is a xanthophyll carotenoid pigment highly valued for its nutraceutical potential. It is a strong antioxidant with wide applications in food, feed, cosmetic and pharmaceutical industries. Zeaxanthin is produced by many Cyanophycean microalgae, but very few zeaxanthin accumulating strains have been reported. In this study, a two-step statistical optimization strategy involving Plackett-Burman (PB) design and response surface methodology (RSM) were successfully utilized to optimize the BG11 culture medium components for enhanced zeaxanthin production from marine Cyanophycean microalgae, Synechococcus marinus (NIOT- 208). The media components (independent variables) of BG11 medium was screened using Plackett-Burman design to identify three crucial nutrients (Na2EDTA, K2HPO4 and NaNO3), which significantly enhanced zeaxanthin yield. Central composite design (CCD) of response surface methodology was used to optimize the concentration of significant variables. The experiments were designed using “Design Expert” software version 9.03 and the results were analyzed using two way ANOVA and a high coefficient of determination (R2=0.984) with a low p value (0.002) indicates that the results are reliable and significant (p<0.05). Validation experiments performed with optimized medium ingredients, NaNO3 (250 mg L-1), K2HPO4 (40 mg L-1) and Na2EDTA (14 mg L-1) enhanced the zeaxanthin yield to 14.61 ± 1.29 mg L-1 which is very close to the predicted value of 14.48 mg L-1. The high zeaxanthin yield accomplished by culture medium optimization resulted in 8.46 fold increase in zeaxanthin yield when compared to BG-11 medium (1.72 ± 0.22 mg L-1). The two-step statistical optimization of culture medium thus facilitated enhanced zeaxanthin yield in S. marinus. Further, the present study has also demonstrated purification of zeaxanthin using preparative RP-HPLC and the purified zeaxanthin was characterized using FT-Raman spectroscopic analysis and HR-MS. RP-HPLC of purified zeaxanthin indicated a high resolution molecular mass of 568.31 daltons and FT Raman spectroscopy analysis yielded three strong Raman bands corresponding to C=C stretching, C–C stretching and C–CH3 at 1537, 1173 and 1032 cm−1 respectively, which are characteristic to the carotenoid zeaxanthin.